2018
DOI: 10.1016/j.celrep.2018.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Hippocampal Place Cell Activity by Single-Cell Stimulation in Freely Moving Mice

Abstract: Learning critically depends on the ability to rapidly form and store non-overlapping representations of the external world. In line with their postulated role in episodic memory, hippocampal place cells can undergo a rapid reorganization of their firing fields upon contextual manipulations. To explore the mechanisms underlying such global remapping, we juxtacellularly stimulated 42 hippocampal neurons in freely moving mice during spatial exploration. We found that evoking spike trains in silent neurons was suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
105
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 51 publications
5
105
0
Order By: Relevance
“…Previous studies in CA1 have shown that a single episode of intracellular stimulation, that is strong enough to evoke complex spikes associated with dendritic plateau potentials, can create a new place field at the stimulation location in head‐fixed mice (Bittner et al, ; Bittner, Milstein, Grienberger, Romani, & Magee, ). A recent study also has shown that juxtacellular stimulation, that is strong enough to induce complex spikes in CA3 or CA1 neurons, can create a new place field at the stimulation location in freely‐moving mice (Diamantaki et al, ). The stimulation effects on CA3 versus CA1 neurons were not compared quantitatively in this study, hence it is unclear whether and how spatial firing stability differs between CA3 and CA1 neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in CA1 have shown that a single episode of intracellular stimulation, that is strong enough to evoke complex spikes associated with dendritic plateau potentials, can create a new place field at the stimulation location in head‐fixed mice (Bittner et al, ; Bittner, Milstein, Grienberger, Romani, & Magee, ). A recent study also has shown that juxtacellular stimulation, that is strong enough to induce complex spikes in CA3 or CA1 neurons, can create a new place field at the stimulation location in freely‐moving mice (Diamantaki et al, ). The stimulation effects on CA3 versus CA1 neurons were not compared quantitatively in this study, hence it is unclear whether and how spatial firing stability differs between CA3 and CA1 neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown more stable spatial firing in CA3 than CA1 over time (Mankin et al, ; Manns, Howard, & Eichenbaum, ) and in response to ventral tegmental area stimulation (Martig & Mizumori, ) and reward location changes (Dupret, O'Neill, Pleydell‐Bouverie, & Csicsvari, ). Nevertheless, the study by Diamantaki et al () suggests that it is possible to induce long‐lasting changes in CA3 spatial firing by artificially activating CA3 pyramidal neurons. Our mossy fiber stimulations may have failed to create permanent place fields because they came short of generating sufficiently strong complex spikes, even at 50 Hz, due to accordingly increased feedforward inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…9 When both initial ramp amplitude and relative input timing are considered, it is apparent 10 that the preferred conditions for large synaptic depression are that spatial inputs 1) have 11 already been strengthened by previous plasticity, resulting in elevated postsynaptic 12 depolarization at the time of presynaptic spikes, and 2) are activated within a time window 13 ~2 -4 seconds away from a plateau ( Fig. 1J, trace color indicates initial ramp amplitude; 14 Fig 1K; two-dimensional interpolation from data, trace color indicates change in ramp 15 amplitude, see Materials and Methods). In summary, BTSP can either strengthen or 16 weaken synapses in a small number of trials, providing a bidirectional learning 17 mechanism capable of both rapid memory storage and erasure.…”
Section: D)mentioning
confidence: 99%
“…To account for the long time course of BTSP, both models (1,3,15,16,18). 13 Biologically, these traces could correspond to the enzymatic activity of calcium- 14 dependent kinases and phosphatases, and post-translational modification and synaptic 15 localization of proteins that regulate synaptic function (18)(19)(20)(21)(22)(23). While in the voltage- 16 dependent model, the amplitudes of these eligibility signals were modulated by the 17 value of postsynaptic depolarization at the time of presynaptic activation ( Fig.…”
Section: D)mentioning
confidence: 99%
See 1 more Smart Citation